Designing Ziswaf-Based Financing Model for Enhancing Micro, Small, and Medium Enterprises - Lili Puspita Sari; Ade Nur Rohim; Fadhli Suko Wiryanto; Dzaky Ammar Fauzi (Journal of Islamic Economics and Finance Studies, 2023)
Micro, Small, and Medium Enterprises (MSMEs) are important in advancing the economy. However, among some existing MSME actors, many of them face obstacles in developing their businesses. Some of those obstacles are the lack of competence and expertise, the lack of business networks, and the limited amount of capital. This research aims to design the development of a sharia financing model based on using zakat, infaq, sadaqah, and waqf (ziswaf) funds to develop MSMEs. This research uses qualitative methods by analyzing various data collected from several works of literature related to ziswaf and MSME studies. This research produces a design model for integrated ziswaf management in the MSME development program. This model describes the process flow starting from collecting ziswaf funds, with a distribution process that is adjusted to the characteristics of the funds. ZIS funds are channeled to the procurement of goods and business equipment, as well as to capacity-building programs for MSMEs. The waqf funds are distributed in the form of business capital investment with a mudharabah agreement. The profits received are given to the nazhir according to the agreement, to be managed by the nazhir, and distributed to the mauquf alaih. The entire process is carried out with supervision and monitoring to maintain conformity of procedures with existing rules and regulations. It is hoped that this model can become a new direction for the development of MSMEs by optimizing ziswaf funds in an integrated manner.   Usaha Mikro, Kecil, Menengah (UMKM) merupakan unit ekonomi yang penting dalam memajukan perekonomian. Namun, di antara sejumlah pelaku UMKM yang ada, banyak dari mereka menghadapi kendala dalam pengembangan usahanya. Di antara kendala yang dihadapi antara lain terkait minimnya kompetensi dan keahlian, minimnya jejaring usaha, hingga jumlah modal yang terbatas. Penelitian ini bertujuan untuk mendesain pengembangan model pembiayaan syariah berbasis pemanfaatan dana zakat, infak, sedekah, dan wakaf untuk pengembangan UMKM. Penelitian ini menggunakan metode kualitatif dengan menganalisis berbagai data yang dihimpun dari beberapa literatur terkait kajian ziswaf dan UMKM. Penelitian ini menghasilkan sebuah rancangan model pengelolaan ziswaf terintegrasi pada program pengembangan UMKM. Model tersebut menggambarkan alur proses yang dimulai dari penghimpunan dana ziswaf, dengan proses penyaluran yang disesuaikan dengan karakteristik dana. Dana ZIS disalurkan pada pengadaan barang dan perlengkapan usaha, serta pada program peningkatan kapasitas pelaku UMKM. Adapun dana wakaf disalurkan dalam bentuk investasi modal usaha dengan akad mudharabah. Keuntungan yang diterima diberikan kepada nazhir sesuai dengan kesepakatan, untuk nantinya dikelola oleh nazhir dan disalurkan kepada para mauquf alaih. Keseluruhan proses tersebut dilakukan dengan pengawasan dan monitoring untuk menjaga kesesuaian prosedur dengan aturan dan ketentuan yang ada. Model ini diharapkan dapat menjadi arah baru pengembangan UMKM dengan mengoptimalkan dana ziswaf secara terintegrasi.